Essential oils for antimicrobial and antioxidant applications in fish and other seafood products - Hassoun, Abdo; Coban, Ozlem Emir (Elsevier Science London, 2017)
Background: Fish and other seafoods are highly perishable food products due basically to microbiological growth and lipid oxidation, which are known to be the principal causes of quality deterioration of such products. Therefore, offering safe and high quality seafoods combined with consumers' desire for natural products free from chemical preservatives creates real challenging problems. In the recent past, there has been extensive focus on antioxidant and antimicrobial effects of natural preservatives such as essential oils (EOs), as effective alternative to synthetic additives, in order to enhance oxidative and microbial stability of foods and extend their shelf life. Scope and approach: In this review, the main spoilage mechanisms of fish and seafood products and the most common techniques used to preserve quality and extend shelf life of such products are first discussed. The chemistry and modes of action of some selected EOs are then briefly presented. The anti oxidative and antimicrobial activities of some common EOs, either alone or in combination with other preservative systems, in fish and other seafoods are reviewed. Finally the limitations and the future trends are shown. Key findings and conclusions: Several EOs have shown i) great antimicrobial activities versus many spoilage and pathogenic microorganisms, and ii) remarkable antioxidant powers against lipid oxidation in fish and other seafoods during processing or storage. However, much more works are still required in order to better understand the exact mechanism of action of EOs or their main components, the effective dose, and the best combination strategy. Published by Elsevier Ltd.
Keywords: Fish; Preservation; Oxidation; Quality; Shelf life; Microbial spoilage; Natural additives